Generating Context Acquisition Code using Awareness API - Duarte, Paulo A. de S.; Peixoto, Maria J. P.; Frota, Yuri S. F.; Viana, Windson (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2017)
Development of Context-Aware and Mobile applications have signicant challenges, such as the complexity of sensor access code and the heterogeneity of devices. THe Google Awareness API is an initiative to mitigate this complexity. This paper presents an analysis of GitHub projects involving Awareness API. However, the results showed that the spread of this API among the developers community is still incipient. We propose to extend a tool to allow high-level modeling of context acquisition and code generation compatible with Awareness API. It reduces the complexity of acquiring contextual information and managing contextual rules.